ANALISIS SISTEM PENGELOLAAN KEUANGAN DAERAH KABUPATEN MINAHASA PROPINSI SULAWESI UTARA - Natalia Rumagit; Stanny Sicilia Rawung (Jurnal Equilibrium, 2020)
Signs that PAD must become the largest share of financial resources for the implementation of regional autonomy shows that PAD is the most important measure for the ability of regions to organize and realize regional autonomy. In addition, PAD also reflects the independence of a region. This study found that the contribution of original regional revenue to total regional revenue during the analysis period from the 2009/2010 - 2019 fiscal year was an average of only 3.48%, with an average growth rate of 21.53%. When compared with the contribution of PAD of cities / districts nationally which is 12%, and the contribution of PAD of cities / regencies in North Sulawesi Province which is 6.3%, it can be said that the contribution of PAD to TPD in Minahasa Regency is still below the national average and North Sulawesi Province. By category, Minahasa District has a very low degree of fiscal autonomy, and is still very dependent on financial contributions and assistance from the central government.